Effectiveness Of Investigations According To Act No. 23 Of 2004 On Domestic Violence Cases - Aryani Nur Chamidah; Ira Alia Maerani (Universitas Islam Sultan Agung, 2021)
This study aims to analyze more deeply the investigation of cases of Domestic Violence that occurred in Grobogan which until now has not been effective. The approach used is sociological juridical. Based on the analysis of the existing data, it was found that the implementation of the investigation in the case of Domestic Violence in Grobogan in its development could not be said to be effective. This is because there are still many families or households who do not know that domestic violence is no longer a family matter but has become a public matter, even a violation of human rights and threatens human life. Besides, there are still many law enforcement officers who are not familiar with the Domestic Violence Law. So that there are obstacles for the process of investigating domestic violence cases when victims report to the RPK (Special Service Room) located at the Regional Police Sergeant in each province in Indonesia. Many investigators have not yet carried out the legal service process for victims by carrying out protective procedures specifically stipulated by Act No. 23 of 2004. This has caused victims to withdraw or withdraw their reports and complaints. The legal facilities provided by the Protection Unit have not been implemented properly.